TERRITORIAL DISPARITIES CAUSED BY THE CURRENT SITUATION OF THE TECHNICAL INFRASTRUCTURE IN RURAL AREAS - CENTRAL REGION - Chitea, Mihai (Economics of Agriculture, 2012)
At European level, the arrangement of the territory is defined as "a spatial expression of the economic, social, cultural and ecologic policies of all societies" ("European Charter of the arrangement of the territory" - 1983). In Romania, the arrangement of the territory and urbanism activities are regulated by the Law 350/2001 regarding the arrangement of the territory and urbanism, with the afterwards changes, which sets the following objectives for the arrangement of the territory: social and economic balanced development of the regions and areas, in compliance with their specificity, improvement of the quality of life for people and human collectivities, responsible management of the natural resources and environmental protection, rational use of the territory.